Wind tunnel study of separated and reattaching flows by particle image velocimetry and pressure measurements. Issue 7 (May 2019) - Shu, ZR; Li, QS
This article presents a comprehensive investigation on the separated and reattaching flows over a blunt flat plate with different leading-edge shapes by means of particle image velocimetry and surface pressure measurements. Wind tunnel tests are performed in both smooth and various turbulent flow conditions, and the separated and reattaching flows are examined as a function of Reynolds number ( Re ), leading-edge shape, turbulence intensity, and turbulence integral length scale. It is shown through the particle image velocimetry and pressure measurements that the Reynolds number effect is significant regarding the mean vorticity field, but with little effect on the mean velocity field. For the effects of leading-edge shape, the distributions of pressure coefficients respond strongly to the change in leading-edge angle, and both the velocity (streamwise and vertical) and vorticity fields have a clear dependence on the leading-edge shape. For the effects of freestream turbulence, the mean pressure coefficient responds strongly to turbulence intensity, whereas the fluctuating and peak suction pressure coefficients are dependent on both turbulence intensity and integral length scale. The size of the separation bubble contracts aggressively with increasing turbulence intensity, but it remains approximately invariant in response to the change in turbulence scale in the tested range.